Ken Leap for Assembly Fundraiser - Watkins, Howard K. (1976)
Donna McKittrick, D B McCrummen, Carol Bequette, Chris Petersen, Lois Ehrenberg all facing camera, Barbara Persigian in white dress, Wanda Wimer